Mastectomy trends for early-stage breast cancer: a report from the EUSOMA multi-institutional European database - Garcia-Etienne, Carlos A.; Heil, Jörg (European journal of cancer, 2012)
Introduction: Recent single-institution reports have shown increased mastectomy rates during the last decade. Further studies aiming to determine if these reports could be reflecting a national trend in the United States of America (US) have shown conflicting results. We report these trends from a multi-institutional European database. Patients and methods. Our source of data was the eusomaDB, a central data warehouse of prospectively collected information of the European Society of Breast Cancer Specialists (EUSOMA). We identified patients with newly diagnosed unilateral early-stage breast cancer (stages 0, I or II) to examine rates and trends in surgical treatment. Results: A total of 15,369 early-stage breast cancer cases underwent surgery in 13 Breast Units from 2003 to 2010. Breast conservation was successful in 11,263 cases (73.3%). Adjusted trend by year showed a statistically significant decrease in mastectomy rates from 2005 to 2010 (p=0.003) with a progressive reduction of 4.24% per year. A multivariate model showed a statistically significant association of the following factors with mastectomy: age <40 or ⩾70years, pTis, pT1mi, positive axillary nodes, lobular histology, tumour grade II and III, negative progesterone receptors and multiple lesions. Conclusion: Our study demonstrates that a high proportion of patients with newly diagnosed unilateral early-stage breast cancer from the eusomaDB underwent breast-conserving surgery. It also shows a significant trend of decreasing mastectomy rates from 2005 to 2010. Moreover, our study suggests mastectomy rates in the population from the eusomaDB are lower than those reported in the US.